Design and fabrication of pneumatic walking robot - Norsyamsul Syazwan, Mohd Nuji (2007)
This report is based on the study about final year project, design and fabrication of pneumatic walking robot. The objective is to design a four legs robot using pneumatic actuator and fabricate the robot structure. In this project, the use of programming logical control software as robot legs motion controller and using pneumatic actuator to move the legs robot. This project need a study about an existing robot in order to produce a moving four legs robot, that only use four actuators because an existing four legs robot use many actuators. Normally eight actuators are use in designing a moving four legs robot. By creative thinking, four legs robot can be design for only four actuators. The method used is divided into two chapters. The first method is by using the SolidWork software to design the robot's legs and body. The second method is verify the way of robot's motion tests by making a ladder diagram program with the Programming Logical Control (PLC) software. Lastly, a four legs robot's model is produced. The problems encountered were discussed.